Genome-Wide Selection Signal Analysis to Investigate Wide Genomic Heredity Divergence between Eurasian Wild Boar and Domestic Pig - Xinming Wu; Haoyuan Zhang; Haoyuan Long; Dongjie Zhang; Xiuqin Yang; Di Liu; Guangxin E (Animals, 2023)
As important livestock species, pigs provide essential meat resources for humans, so understanding the genetic evolution behind their domestic history could help with the genetic improvement of domestic pigs. This study aimed to investigate the evolution of convergence and divergence under selection in European and Asian domestic pigs by using public genome-wide data. A total of 164 and 108 candidate genes (CDGs) were obtained from the Asian group (wild boar vs. domestic pig) and the European group (wild boar vs. domestic pig), respectively, by taking the top 5% of intersected windows of a pairwise fixation index (FST) and a cross population extended haplotype homozygosity test (XPEHH). GO and KEGG annotated results indicated that most CDGs were related to reproduction and immunity in the Asian group. Conversely, rich CDGs were enriched in muscle development and digestion in the European group. Eight CDGs were subjected to parallel selection of Eurasian domestic pigs from local wild boars during domestication. These CDGs were mainly involved in olfactory transduction, metabolic pathways, and progesterone-mediated oocyte maturation. Moreover, 36 and 18 haplotypes of INPP5B and TRAK2 were identified in this study, respectively. In brief, this study did not only improve the understanding of the genetic evolution of domestication in pigs, but also provides valuable CDGs for future breeding and genetic improvement of pigs.